The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1101/392399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein Kinase A activity is regulated by actomyosin contractility during cell migration and is required for durotaxis

Abstract: Dynamic subcellular regulation of Protein kinase A (PKA) activity is important for the motile behavior of many cell types, yet the mechanisms governing PKA activity during cell migration remain largely unknown. The motility of SKOV-3 epithelial ovarian cancer (EOC) cells has been shown to be dependent on both localized PKA activity and, more recently, on mechanical reciprocity between cellular tension and extracellular matrix (ECM) rigidity. Here, we investigated the possibility that PKA is regulated by mechan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Through these signalling networks, effector proteins like PKA and YAP become activated, leading to changes in protein activation and dynamics, as well as gene expression changes, which are crucial for normal durotaxis [79,80].…”
Section: Durotactic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through these signalling networks, effector proteins like PKA and YAP become activated, leading to changes in protein activation and dynamics, as well as gene expression changes, which are crucial for normal durotaxis [79,80].…”
Section: Durotactic Mechanismsmentioning
confidence: 99%
“…In durotaxis, stress fibre contractility, which is normally mediated by RhoA, is the means by which forces are applied on the substrate [28]. Active RhoA also controls fast cellular retraction during durotaxis [79]. These activities of RhoA are also evident and required for haptotaxis and chemotaxis [109,110].…”
Section: Many Stimuli: Common Effectors?mentioning
confidence: 99%
“…In a novel microfluidic device, when mechanically flow osteocytes were adjacent to breast cancer cells, breast cancer extravasation was significantly reduced with mechanically stimulated osteocytes compared to static osteocytes, though the breast cancer cells remained under static conditions (Mei et al, 2019). When considering the effects of strain, 2D stretching is typically applied acutely and held steady for a period of time with a variety of results across multiple cell types (Gao & Carson, 2016; Manome et al, 2003; McKenzie et al, 2020; Panzetta et al, 2019; Riching et al, 2014). One study reported that 2D cyclic compression of breast cancer cells plated underneath an agarose gel by a platen regulated necrosis vs apoptosis, and the mode of death was sensitive to loading frequency, peak applied compressive displacement, and duration of loading bout (Takao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We performed two-color pcSOFI with DrFLINC-AKAR and Lifeact-Dronpa in HeLa cells and found that with the exception of filopodia, the majority of PKA activity microdomains did not colocalize with actin (Figure 4B/E). These data suggest that PKA activity microdomains are not generally organized along actin networks, but instead more specifically targeted to sub-regions that are involved in migration and mechano-sensing [21][22] .…”
mentioning
confidence: 96%